2020
DOI: 10.21203/rs.2.16479/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between maternal BMI, breastfeeding practices and infant anthropometric status in Colombia; secondary analysis of ENSIN 2010.

Abstract: • Background: Maternal malnutrition and infant feeding mode impact short and long term infant and child morbidity and mortality. The period of lactation may provide an opportunity to modulate the risk of disease later in life. Our aim was to estimate the effect of maternal body mass index (BMI) and infant feeding mode, particularly breastfeeding practices, on the anthropometric status of children under two years in Colombia.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…BMI explains about 17 % of the gap. Empirical studies consistently show the association between maternal BMI and child stunting (52)(53)(54)(55) . The pathway in which underweight status affects subsequent anthropometric failure of the child starts in utero.…”
Section: Discussionmentioning
confidence: 96%
“…BMI explains about 17 % of the gap. Empirical studies consistently show the association between maternal BMI and child stunting (52)(53)(54)(55) . The pathway in which underweight status affects subsequent anthropometric failure of the child starts in utero.…”
Section: Discussionmentioning
confidence: 96%
“…Various factors are related to the occurrence of undernutrition in children aged under 5 years, such as the mother's education, a low birth weight, the child's gender, and the absence of breastfeeding (Aldana‐Parra et al, 2020; Choudhury et al, 2017; Mekonen et al, 2019; Murarkar et al, 2020). Among these risk factors, breastfeeding was confirmed to be an important protective factor for preventing undernutrition (Ahsan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between breastfeeding and undernutrition among children remains unclear with some studies supporting a significant association between breastfeeding and undernutrition (Ansuya et al, 2018; Berhe et al, 2019; Campos et al, 2020) and other studies reporting inconsistent findings (Aldana‐Parra et al, 2020; Meshram et al, 2011; Syeda et al, 2020). Among those studies, the duration of breastfeeding [i.e., less than 4 months (Ambadekar & Zodpey, 2017) or more than 6 months (Ahsan et al, 2017)], different types of undernutrition [i.e., wasting (Paré et al, 2019), stunting (Ahsan et al, 2017), or being underweight (Ansuya et al, 2018)] might explain the inconsistencies.…”
Section: Introductionmentioning
confidence: 99%
“…19 Many studies have confirmed the significance of maternal dietary status, particularly for the duration of the perinatal period, on toddler dietary status (first one thousand days of life). [20][21][22] This relationship has been investigated in studies in which BMI before pregnancy undoubtedly correlated with start weight, duration, and head circumference (β=0.274, 0.094, and 0,101, respectively; p<0.05 in all instances. 23 Additionally, maternal nutritional status can be used to predict malnutrition in toddlers at the age of 6 to 12 months.…”
Section: Articlementioning
confidence: 99%